Development of an Inquiry-Based Student Worksheets on the Topic Plants as Sources of Life on Earth for Elementary School Students: - - Tamalene, Asri; Pamuti, Pamuti; Asrun, Nadila (JURNAL BIOEDUKASI, 2025)
Abstrak The development of inquiry-based Student Worksheets (LKPD) was carried out as an effort to create learning that places students as active subjects in discovering concepts independently. This study aims to develop student worksheets inquiry-based on the material of plants as sources of life on earth that are valid, feasible, and practical for learning at SD Negeri 1 Kota Ternate. The method used in this study was a research and development method adapted from Borg & Gall, which included the stages of data/information collection, product planning, initial product development, product validation and testing, and final product. The results of the study showed that the developed student worksheets met the criteria of being highly valid. Based on the validation results by subject matter experts, a score of 4.8 was obtained, which is considered highly valid. The validation results by media experts obtained a score of 4.1, which is considered valid, while the practicality assessment results obtained a score of 88%, which means that the inquiry-based LKP developed is very feasible for use. This means that the student worksheets developed can be used in science learning. The flip book learning media is highly valid and very feasible for use. Keywords: student worksheet; iquiry learning; students; plant